The role of tax agents in sustaining the Malaysian tax system - Mohd Isa, Khadijah; Yussof, Salwa Hana; Mohdali, Raihana (Elsevier Ltd., 2014)
In Malaysia, a self-assessment system has been implemented for all companies for more than a decade.The system necessitates corporate taxpayers to declare and calculate accurate sources of income, estimate income tax payable, keep records for audit purposes, and comprehend income tax legislation.In complying with these demands, many corporate taxpayers have to depend on the assistance of tax agents.Using survey data, this study aims to examine the role of tax agents in sustaining the SAS in Malaysia.This study enhances the understanding of the scope of tax agents’ involvement under the system. Findings from this study are predominantly positive and should be beneficial for policy makers in their efforts to review and modify current tax systems.